Do discontinuities in marginal reimbursement affect inpatient psychiatric care in Germany? - Clara Pott; Tom Stargardt; Udo Schneider; Simon Frey (The European Journal of Health Economics, 2020)
This paper examines the behaviour of mental health care providers in response to marginal payment incentives induced by a discontinuous per diem reimbursement schedule with varying tariff rates over the length of stay. The analyses use administrative data on 12,627 cases treated in 82 psychiatric hospitals and wards in Germany. We investigate whether substantial reductions in marginal reimbursement per inpatient day led to strategic discharge behaviour once a certain length of stay threshold is exceeded. The data do not show gaps and bunches at the duration of treatment when marginal reimbursement decreases. Using logistic regression models, we find that providers did not react to discontinuities in marginal reimbursement by significantly reducing inpatient length of stay around the threshold. These findings are robust in terms of different model specifications and subsamples. The results indicate that if regulators aim to set incentives to decrease LOS, this might not be achieved by cuts in reimbursement over LOS.
Keywords: 610; Health care financing; Prospective payment system; Length of stay; Marginal payment incentives; Hospital behaviour; Mental health care; Analysis of health care markets (I11); Government policy; Regulation; Public health (I18)